Analisis Pengaruh Variasi Produk, Fasilitas Dan Kualitas Pelayanan Terhadap Minat Beli Ulang Konsumen Mie Gacoan (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2019) - Sahrizal Avan Malik; Muhammad Ridwan Basalamah; Nanik Wahyuningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine the effect of product variations, facilities, and service quality on repurchase intention among consumers of Gacoan noodles in Malang. This study uses a quantitative approach. The study uses primary data obtained by 90 respondents as a sample selected based on the purposive sampling method. The collected data were analyzed based on multiple linear regression analysis using SPSS. The results of this study indicate that product variations, facilities, and service quality have a significant effect simultaneously on repurchase intention. The product variety has a positive and significant influence on repurchase intention. Facilities and service quality have a positive and not significant effect on repurchase intention. Keywords: Product Variation, Facilities, Service Quality, Repurchase Intention